Enhancement in Optical Properties of Lanthanum-Doped Manganese Barium Hexaferrites under Different Substitutions - Meshal Alzaid (Advances in Condensed Matter Physics)
The permeability and electrical resistivity of barium hexaferrite magnetic materials can be used in various products such as magnetic recording media, computers, electronic devices, materials for permanent magnets, and communication devices. This work focuses on the synthesis of rare earth lanthanum (La3+)-doped manganese in barium hexaferrite (Ba1−xLaxMnyFe12−yO19) (x = 0.02–0.10 and y = 0.02–0.10) prepared by using the coprecipitation method. The intensity peak is increased with increasing the concentration of lanthanum, which shows the enhancement in the degree of crystallinity and increase in the size of crystallite. The band gap energy decreased gradually with the increase of concentration of lanthanum. The micrographs observed that the material is basically made up of some rings or rods such as particles in pure La-Ma in barium hexaferrite. The agglomeration was observed because of heat behavior at 600°C or may be concentration effect. The structural studies are done using X-ray diffraction, UV, FT-IR, and SEM techniques.